2018
DOI: 10.1007/s00467-018-4036-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on dyslipidemia and carotid intima-media thickness in children with refractory nephrotic syndrome: a randomized controlled trial

Abstract: Atorvastatin, administered at a fixed daily dose of 10 mg, was not beneficial in lowering lipid levels in children with SRNS; rise in serum albumin was associated with improvement in dyslipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…This can be translated into less than expected efficacy, and thus lower CVD risk reduction that imposes a need for treatment change. 22,25 On the other hand, in a study with rosuvastatin, efficiency was equal for children above or below 10 years old with atorvastatin, 4 and it was similar regardless of age/ezetimibe use/apheresis. 3 In a simvastatin study, 21 simvastatin was given for children with mild typical Smith-Lemli-Opitz syndrome (SLOS; autosomal recessive multiple cognitive impairment syndrome characterized by accumulation of a cholesterol precursor due to gene mutation(s) of a related enzyme) concurrently with dietary cholesterol supplementation, and was found to be effective even in decreasing cerebrospinal fluid, levels of cholesterol (simvastatin is lipophilic and can enter blood-brain barrier), and children irritability (symptom of SLOS).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…This can be translated into less than expected efficacy, and thus lower CVD risk reduction that imposes a need for treatment change. 22,25 On the other hand, in a study with rosuvastatin, efficiency was equal for children above or below 10 years old with atorvastatin, 4 and it was similar regardless of age/ezetimibe use/apheresis. 3 In a simvastatin study, 21 simvastatin was given for children with mild typical Smith-Lemli-Opitz syndrome (SLOS; autosomal recessive multiple cognitive impairment syndrome characterized by accumulation of a cholesterol precursor due to gene mutation(s) of a related enzyme) concurrently with dietary cholesterol supplementation, and was found to be effective even in decreasing cerebrospinal fluid, levels of cholesterol (simvastatin is lipophilic and can enter blood-brain barrier), and children irritability (symptom of SLOS).…”
Section: Resultsmentioning
confidence: 94%
“…In all trials studying efficacy and/or safety, children enrolled were generally 8 years old and above, except for some studies that lowered the age range to reach 4 year olds for simvastatin, 21 5 years old for atorvastatin, 22 and 6 year olds for rosuvastatin, 3 atorvastatin, 4 and pitavastatin. 23 All of these studies had not reported any safety issues or discontinuations, and if present, they were not related to any adverse side effect encountered.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations